Rancang Bangun Panel Photovoltaic Dengan Automatic Sun Tracking System (Asts) Untuk Mengoptimalan Serapan Energi Matahari - Dewantara, Belly Yan; Rahmatullah, Daeng (J-Eltrik, 2019)
Nowadays solar panel is widely used as an independent power plant, it can be seen the many applications of solar panels on electrical equipment, such as traffic light, general lighting, etc. The energi produced by solar panel is affected by the absorbed sunlight. generally solar panels are implemented statically, this causes the absorption of solar energi is not maximal in the morning and afternoon. To maximize the absorption of sunlight, solar panels must always be facing perpendicular to the position of the sun. Automatic solar tracking system is needed to solve these problems, It is makes solar panels always perpendicular to the sun and can follow the movement of the sun, so that the absorption of solar energi is more leverage. The results of the test show the use of automatic tracking system to get the maximum absorption of solar energi indicated by a more stable voltage output,and the power generated is greater than using a static solar panel. Automatic Sun Tracking System (ASTS) increase the average power up to Â± 39-41 watt / day with the efficiency of ASTS 81.66% on PV panel 50 WP.